Az itt-és-most létállapot támogatása a reflexiós folyamatban - GORBAI, Gabriella Márta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
The here and now State of Mind in the Reflection Process. Teachers need to have ‘total encounters’ with pupils in order to have a pedagogic impact. Yet, during the teaching period students often claim as a problem the lack of „presence” while they are teaching. This study deals with the question of how student teachers could reach the capacity for presence during their lessons, which strengthens the development of their professional behaviour. We present an approach to reflection which provides a more balanced attention to thinking, feeling and wanting as the sources of behaviour and we emphasize the shift in the content of reflection from the past to the ideal future, and the focus on presence and mindfulness. We believe that the full awareness of the here-and-now that presence is about, encompasses and connects both the teacher’s self – and his or her strengths –, and the environment.